Characterization and immunoprotection of thioredoxin reductase TrxB knockout mutant of Salmonella Enteritidis - Zhu, Siping; Wang, Lili; Li, Hong; Li, Chihuan; Zhu, Xintong; Ren, Chao; Liu, Xiaochen; Dong, Yulai; Shi, Qiumei; Zhang, Zhiqiang (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundSalmonella Enteritidis (S. Enteritidis) is an important zoonotic pathogen that poses a major threat to animals and human health. TrxB, as a key component of the thioredoxin system, is a thioredoxin reductase ubiquitously present in organisms. It is mainly involved in maintaining cellular redox balance, but its role in the pathogenicity of S. Enteritidis remains unclear.MethodsIn this study, we generated a trxB-deficient strain from S. Enteritidis C50336 strain to investigate how TrxB affects the biological characteristics and pathogenesis of the bacterium. The virulence of ΔtrxB was assessed by measuring ΔtrxB resistance to environmental stress, biofilm formation ability, motility, adhesion, invasion ability, intracellular survival, LD50, virulence gene expression levels, and in vivo colonization ability. Additionally, the study measured specific IgG antibody levels in mice, lymphocyte proliferation, and the immunoprotective effect of ΔtrxB.ResultsWe found that deletion of trxB gene did not affect the growth and biochemical properties of the S. Enteritidis strain but significantly reduced its motility, drug resistance, biofilm formation, and tolerance to environmental stress. After trxB knocked out, the adhesion and invasion capacities of S. Enteritidis to Caco-2 cells, along with its proliferation in RAW264.7 cells, were significantly reduced. Additionally, the trxB-deficient strain exhibited significantly lower pathogenicity than the parental strain, evidenced by a more than 100-fold increase in LD50. We also observed a significant decrease in the expression of virulence-related genes in the trxB-knockout mutant. More importantly, immunization with this deletion strain can confer promising protection against challenge with the C50336 strain.ConclusionThese findings indicate that TrxB is a crucial virulence factor in S. Enteritidis, playing critical roles in its pathogenicity.